Colistin broth disk elution for the detection of Colistin resistance among Carbapenem-resistant Klebsiella pneumoniae - Phu Thien Truong; Ngoc Bich Tran; Hoang Huy Pham; Van Thi Hue Tran; Hoang Thanh Phan; Binh Thai Pham; Lam Thi Ngoc Tran; Truc Thi Thanh Nguyen; Mai Le Phuong; Dat Quoc Ngo (Revista Cubana de Medicina Militar)
Introduction: The emergence of multidrug-resistant pathogens, especially carbapenem-resistant Klebsiella pneumoniae (CRKP), is a pressing public health issue. The limited therapeutic choices further compound this. The escalating resistance to colistin, a crucial last-resort antibiotic, underscores the need for precise and dependable antimicrobial susceptibility testing (AST) methods. Objectives: To evaluate the performance of the Colistin Broth Disk Elution (CBDE) method in comparison to the reference Broth Microdilution (rBMD) method for detecting colistin resistance in CRKP isolates. Methods: A cross-sectional study involving 129 non-duplicate CRKP isolates was conducted at Cho Ray Hospital from October 2023 to December 2023. Colistin susceptibility was assessed using both the BMD and CBDE methods. The agreement between the two methods was measured in terms of categorical agreement (CA) and essential agreement (EA) based on Clinical and Laboratory Standards Institute (CLSI) criteria. Results: Of the 129 CRKP isolates, 23.26 % were identified as colistin-resistant by both BMD and CBDE methods. The CA between the two methods was 100 %, and the EA was 91.47 %, with no major errors (ME) or very major errors (VME) detected. Conclusion: The CBDE method has shown a high level of agreement with the reference BMD method, making it a reliable alternative for the routine detection of colistin resistance in microbiology laboratories. The study's findings strongly support using CBDE as a practical and effective AST method for colistin, thereby contributing to antibiotic stewardship.